2021
DOI: 10.1590/1983-21252021v34n212rc
|View full text |Cite
|
Sign up to set email alerts
|

Biological Nitrogen Fixation Stability of Cowpea Cultivars With Tropical Semi-Arid Rhizobial Strains

Abstract: Cowpeas (Vigna unguiculata L. Walp) are an economically and socially important legume in northern and north-eastern Brazil and can establish effective symbiosis with nitrogen-fixing bacteria. We evaluated the symbiotic compatibility and efficiency of rhizobial strains from Pernambuco semi-arid soils and determined their symbiotic stability on the IPA-206, BR 17-Gurguéia, and BRS Novaera cultivars, selected for different environments. The experiment was conducted in a greenhouse to evaluate a 3 × 28 factorial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Concerning cowpea, four strains are recommended: BR 3267 identified as Bradyrhizobium yuanmingense [ 70 ]; BR 3262 identified as Bradyrhizobium pachyrhizi [ 70 ]; UFLA 03–84 identified as Bradyrhizobium viridifuturi [ 71 ]; and INPA 3-11B identified as Bradyrhizobium elkanii [ 72 ]. Inoculation with these strains may significantly increase BNF contributions from 36 to 75 kg N ha −1 [ 69 , 73 , 74 ]. In Venezuela, Artigas Ramirez et al [ 75 ] found that rhizobia nodulating cowpea are mainly fast growing, including the genera Rhizobium and Ensifer, and the β-rhizobia genera Burkholderia and Paraburkholderia, although Bradyrhizobium has also been found.…”
Section: Microsymbionts Inhabitants Of Pulse Nodulesmentioning
confidence: 99%
“…Concerning cowpea, four strains are recommended: BR 3267 identified as Bradyrhizobium yuanmingense [ 70 ]; BR 3262 identified as Bradyrhizobium pachyrhizi [ 70 ]; UFLA 03–84 identified as Bradyrhizobium viridifuturi [ 71 ]; and INPA 3-11B identified as Bradyrhizobium elkanii [ 72 ]. Inoculation with these strains may significantly increase BNF contributions from 36 to 75 kg N ha −1 [ 69 , 73 , 74 ]. In Venezuela, Artigas Ramirez et al [ 75 ] found that rhizobia nodulating cowpea are mainly fast growing, including the genera Rhizobium and Ensifer, and the β-rhizobia genera Burkholderia and Paraburkholderia, although Bradyrhizobium has also been found.…”
Section: Microsymbionts Inhabitants Of Pulse Nodulesmentioning
confidence: 99%